Electrochemical deposition of complex chromoxide composites on stainless steel - Shtefan, Viktoriia Volodymyrivna; Kanunnikova, Nadiia Oleksandrivna; Dubrovskyi, Vladyslav Stanislavovych (Izdevnieciba "Baltija Publishing", 2023)
The development of modern science and technology requires the creation of the latest composite materials that will work successfully and have an appropriate level of their functional properties under the influence of aggressive environments. Thus, at present, solving the issues of protection of materials and structures of nuclear reactors from various types of corrosion destruction is a priority task, which necessitates the development of new means of protection of corrosion-resistant materials1. One of the effective methods of forming coatings with the necessary set of properties on the surface of metals is the electrochemical method2. With cathodic polarization, non-porous, dense oxide composites are formed on the surfaces of metals, which allow not only to ensure safe operation, but also to significantly reduce the costs of repair and restoration after breakdowns, destruction of products and complex technical systems under the influence of climatic factors3. The composition and properties of oxide composites are determined by the nature of the metal and electrolyte, as well as depend on the conditions of their production, which makes it possible to control the process4.
Keywords: electrochemical deposition; chromoxide composites; stainless steel; composite materials; aggressive environments; corrosion